(3efGgL GdJhSd aj eHGgL GdJQSds - (3YHO GdQMef Hf eMeO Hf Ydj Hf CMeO Hf eMeO GdHSWGej GdMfaj, Rjf GdOjf,J (B858 (3g` s
(3ChdgG (B:s
(3HSe Gddg GdQMef GdQMje hHYO agPg QTMGJ PhbjI , hSHMGf ThbjI ahGFO HMQ GdYdeGA hahGFOgG Yf aNQ GdHdZGA s
(3BNQgG (B:s
(3MedJ ef GdCThGb eG dh MedJg , Ydi cd Cgd GdGQV XdhG Hg NjQkG hgPG BNQ cJGH GdeSei HefGgL GdJhSd ai eHGgL GdJhSd GdeTJed Ydi ahGFO eajOI s
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B331 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B5 - (3U (B184s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1845s
(3eUOQ GbJfGA GdCUd (B:s
(3ESchQjGd (B(523/1) s
Keywords: (3GdCOHs